Influence of different rootstocks on yield precocity and fruit quality of ‘Tarocco Scirè’ pigmented sweet orange - Continella, A.; Pannitteri, C.; La Malfa, S.; Legua, P.; Distefano, G.; Nicolosi, E.; Gentile, A. (Scientia horticulturae, 2018)
•Bitters and Furr affected the yield precocity and fruit quality of ‘Tarocco’ blood orange.•Bitters showed higher yield efficiency and is suitable for higher density planting.•‘Tarocco’ fruit peel pigmentation was enhanced with Poncirus-derived rootstocks.•Rootstock was also effective for enhancing fruit juice pigmentation. Several studies in citrus-producing countries are currently being carried out to select and evaluate rootstocks that are tolerant to Citrus Tristeza Virus (CTV) and can be adopted in different citrus production areas. An evaluation of rootstock suitability must consider the productive and qualitative features as well as the adaptability to varied environmental conditions (i.e., soil characteristics). Additionally, some varieties present qualitative aspects that are appreciated by consumers but can be affected by the use of different rootstocks. In Italy, the qualitative traits of pigmented or blood oranges, which are characterized by the presence of anthocyanins in the peel and flesh, are strongly influenced by several factors, including the scion/rootstock combination. The objective of this study was to evaluate and compare the influence of ten rootstocks on yield precocity and fruit quality of ‘Tarocco Scirè’ pigmented sweet orange in a Sicilian area within the Protected Geographical Indication (GPI) “Arancia Rossa di Sicilia” production district. Five of the ten rootstocks, namely, ‘Bitters’, ‘Carpenter’, ‘Furr’, ‘F6P12®’ and ‘F6P13′, have recently been released and produced good yields in limiting soil conditions. In this study, the important role of rootstock in determining the organoleptic quality, specifically the sugar content, and the anthocyanin concentrations in both the pulp and the juice was demonstrated. Some of the rootstocks that were recently introduced in Italy, i.e., ‘Bitters’ and ‘Furr’, were promising because they positively influenced several agronomic and qualitative parameters in the tested conditions, positively affected the yield precocity and enhanced the fruit juice anthocyanin content. Overall, these results contribute to the assessment of the role of different rootstocks in the post-CTV Italian citrus industry.